Analisis Strategi Pengembangan Objek Wisata Suaya Dalam Upaya Peningkatan Kunjungan Di Kecamatan Sangalla’ Kabupaten Tana Toraja - Reynaldi Batara Londong Allo; Isak Pasulu; Olivia D.Y. Pompeng (Universitas Kristen Indonesia Toraja, 2024)
This study aims to determine the development strategy for the Suaya tourist attraction, Sangalla' District, Tana Toraja Regency, the research method used in this study is descriptive and SWOT analysis, the data used in this study are primary data and secondary data, data collection techniques were conducted by interview , observation and literature study. Based on the results of the study, it showed that the IFAS Matrix obtained a total score of 3.04, this indicated that the internal conditions at the Suaya tourist attraction were in a strong position. The EFAS Matrix obtained a total score of 3.19, this indicates that the external conditions at the Suaya tourist attraction are in a strong position. Based on the results of the IFAS, EFAS matrix analysis, the SWOT diagram shows that the Suaya tourist attraction is in quadrant I, so the right strategy is the SO (Strength Opportunities) strategy and supports aggressive growth policies by taking advantage of existing opportunities and internal strengths owned by Suaya tourism objects.